Measurement of the inelastic pp cross-section at a centre-of-mass energy of 13 TeV - Aaij, Roel; Adeva, B.; Adinolfi, M.; Grünberg, Oliver; Heß, Miriam; Meinert, Nis; Viemann, Harald; Waldi, Roland; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; et al. (Journal of high energy physics, 2018)
The cross-section for inelastic proton-proton collisions at a centre-of-mass energy of 13 TeV is measured with the LHCb detector. The fiducial cross-section for inelastic interactions producing at least one prompt long-lived charged particle with momentum p > 2 GeV/c in the pseudorapidity range 2 < η < 5 is determined to be σacc = 62.2 ± 0.2 ± 2.5 mb. The first uncertainty is the intrinsic systematic uncertainty of the measurement, the second is due to the uncertainty on the integrated luminosity. The statistical uncertainty is negligible. Extrapolation to full phase space yields the total inelastic proton-proton cross-section σinel = 75.4 ± 3.0 ± 4.5 mb, where the first uncertainty is experimental and the second due to the extrapolation. An updated value of the inelastic cross-section at a centre-of-mass energy of 7 TeV is also reported. Open image in new window
Gesehen am 13.06.2019
The LHCb collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Grünberg, M. Heß, N. Meinert, H. Viemann, R. Waldi, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]